2017
DOI: 10.1061/(asce)gt.1943-5606.0001605
|View full text |Cite
|
Sign up to set email alerts
|

Nonparametric Liquefaction Triggering and Postliquefaction Deformations

Abstract: This study evaluates granular liquefaction triggering case-history data using a nonparametric approach. This approach assumes no functional form in the relationship between liquefied and nonliquefied cases as measured using cone penetration test (CPT) data. From a statistical perspective, this allows for an estimate of the threshold of liquefaction triggering unbiased by prior functional forms, and also provides a platform for testing existing published methods for accuracy and precision. The resulting thresho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Post-event earthquake reconnaissance similarly strives to determine if YES the soil failed or NO it did not. These class models are then used to forecast the outcome for future events (e.g., [Moss et al, 2006;Yazdi and Moss, 2017], Smith and Moss, 2021). In concept the shear stiffness should then also provides some utility for debris flow triggering.…”
Section: Shear Stiffness In the Labmentioning
confidence: 99%
“…Post-event earthquake reconnaissance similarly strives to determine if YES the soil failed or NO it did not. These class models are then used to forecast the outcome for future events (e.g., [Moss et al, 2006;Yazdi and Moss, 2017], Smith and Moss, 2021). In concept the shear stiffness should then also provides some utility for debris flow triggering.…”
Section: Shear Stiffness In the Labmentioning
confidence: 99%
“…The questions then becomes, which mechanism controls and how much deformation is expected? For liquefaction deformations Yazdi and Moss (2016) can be used to estimate deformations. For sloping ground or free face conditions it is typical to use a lateral spreading model (Youd et al, 2002).…”
Section: Comparison Of Ground Failure Mechanismsmentioning
confidence: 99%
“…Next to that, due to the magnitude range of the attenuation equations, the seven data samples from the Tohoku earthquake, with a moment magnitude of nine, are eliminated from the dataset. From all of the parameters in the source, only eight are selected according to studies reported in the literature [7,13,15,16,27,28,30,31,[46][47][48][49][50]: momentum magnitude (Mw), PGA(g), thickness of liquefiable soil (m) (measured from critical depth interval)(T), ground water table GWT (m), overburden stress (σ) (kPa), effective overburden stress (σ') (kPa), normalized con penetration test result tip (q c1N ), mean grain size (D 50 ), and fine content (FC) (%). The two extra parameters of CAV and r rup are added to the dataset through Equations (9) and (10), Therefore, the study considers some of the essential aspects of the earthquakes, such as the near-fault earthquake zone and causative fault type of the earthquake.…”
Section: Case History Databasementioning
confidence: 99%
“…In this study, the most essential parameters to evaluate the potential of liquefaction are selected according to background research studies [7,13,15,16,27,28,30,31,[46][47][48][49][50]. Then, two new earthquake parameters added to the dataset to create a comprehensive database: CAV 5 and the closest distance from the site to the rupture surface (r rup ).…”
Section: Introductionmentioning
confidence: 99%